Application of RESTful Web Service in the Development of Letter Management Information System of Inspectorate - Fikri, M Fauzan; Tania, Ken Ditha (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The rapid development of technology can increase efficiency and effectiveness in all fields by optimizing the use of technology. The Inspectorate of South Sumatra Province is a government agency located in the capital city of South Sumatra, Palembang. The problem found in the Inspectorate of South Sumatra Province is the disposition of letters that have not been digitized so that the disposition of letters cannot be monitored and the range of letters is lost. It takes more time and storage in searching for letters. With a system that is still manual, the inspectorate of the province of South Sumatra requires more budget for paper media and a lack of efficiency and effectiveness in the manual system. So a digitized letter management system is needed that can be accessed by mobile devices or PCs. With the Web Service, it is believed that it can support data integration between mobile and PC without third party applications. The application of RESTful API can increase security in user access rights. The results of this study are in the form of applications with the Rapid Application Development method adopting the Unified Modeling Language system design with Blackbox testing, it is known that the application runs well according to user needs, indicating that the application can solve problems in letter management that occur in the inspectorate of the province of South Sumatra.